Effects of Guanidinoacetic Acid, Creatine, and Choline on Protein Deposition and Creatine Status in Growing Cattle - M. S. Grant; M. D. Miesner; E. C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2021)
Objective:This study was conducted to evaluate effects of guanidinoacetic acid and creatine supplementation in the presence or absence of supplemental choline on body creatine status and lean tissue growth. Study Description:Six ruminally-cannulated Holstein steers (321 lb) were utilized in an experiment consisting of six 10-day periods, where each steer received one of six treatments in each period. Treatments were abomasal infusion of a saline solution (control), 15 g/day guanidinoacetic acid, or 16.8 g/day creatine, in combination with 0 or 5 g/day choline, with all treatment combinations represented. Complete collection of urine and feces was conducted to calculate nitrogen retention as a measure of protein deposition. Steers were fed a corn-based diet. Bottom line:Supplementing 15 g/day guanidinoacetic acid increased lean tissue growth in growing steers fed corn-based diets.
Keywords: methyl groups; guanidinoacetic acid; choline